High-heat-resistant pp bead foamed material and preparation method thereof
Patent Information
- Application Number
- CN202611436945.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]为了克服现有PP发泡材料存在的耐热性不足、熔体强度低、蒸汽粘接性差等问题,本申请提供一种高耐热PP珠粒发泡材料及其制备方法
1. 本申请预先采用重量比为(3-5):1的无规共聚聚丙烯与高分子微粉制备母粒A,将其与特定重量比的无规共聚聚丙烯和均聚聚丙烯、高分子粘结改性剂、短切纤维等组分熔融共混,挤出造粒,从而获得了一种综合性优异的高耐热PP珠粒发泡材料,其具有高耐热、高熔体强度、优异蒸汽粘接性及均匀细密泡孔结构等优点,具有广泛的应用前景。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials technology, specifically to a high heat-resistant PP bead foaming material and its preparation method. Background Technology
[0002] Polypropylene (PP) is a thermoplastic with excellent comprehensive performance. It has advantages such as low density, chemical resistance, easy processing and molding, and recyclability. When it is made into foamed materials, it can be further lightweight and endowed with additional functions such as cushioning, sound insulation, and heat insulation. Therefore, it has a wide range of applications in automotive interiors, precision packaging, building insulation, and home appliance cushioning pads.
[0003] Currently, the main industrial methods for preparing PP foam materials include compression molding, extrusion foaming, and bead foaming. Among these, bead foaming involves first producing expandable PP beads, then using a steam forming mold to melt and bond the beads together, ultimately obtaining the desired shape of the foamed product. This method has become the mainstream manufacturing process in the industry due to its ability to produce complex shapes and its wide adjustable expansion ratio. However, existing PP materials still face the following problems in bead foaming applications: First, ordinary polypropylene has low melt strength, making the cell walls prone to rupture during foaming, leading to cell collapse and merging, making it difficult to obtain foamed beads with high expansion ratios and uniform cell structure. Second, the industry typically adds nucleating agents or reinforcing fillers, or uses high-crystallinity or homopolymer PP resins to further improve the heat resistance of PP foamed products. However, this method offers limited improvement in temperature resistance and cannot meet the requirements of high-heat-resistance scenarios. Furthermore, it often results in the surface of the foamed beads being difficult to melt and soften at conventional steam forming temperatures, leading to ineffective bonding between the beads and extremely poor overall mechanical properties.
[0004] Therefore, providing a PP bead foam material that combines high melt strength, high heat resistance, and excellent steam bonding performance is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0005] In order to overcome the problems of insufficient heat resistance, low melt strength and poor steam adhesion of existing PP foam materials, this application provides a high heat-resistant PP bead foam material and its preparation method.
[0006] In a first aspect, this application provides a high heat-resistant PP bead foam material, employing the following technical solution: A high heat-resistant PP bead foam material comprises the following components in parts by weight: 100 parts polypropylene, 1-10 parts compatibilizer, 0.5-10 parts polymer binder modifier, 0.2-2 parts nucleating agent, 2-15 parts chopped fibers, and 5-20 parts masterbatch A; The polypropylene includes random copolymer polypropylene and homopolymer polypropylene in a weight ratio of (80-95):(5-20); The masterbatch A is obtained by melt blending random copolymer polypropylene and polymer micro powder in a weight ratio of (3-5):1, extrusion granulation and drying. The polymer micro powder is selected from one or more of polytetrafluoroethylene micro powder, polyethylene terephthalate micro powder, polybutylene terephthalate micro powder, and polyamide micro powder; the particle size of the polymer micro powder is 10-100 μm.
[0007] This application uses a specific ratio of random copolymer PP and homopolymer PP as the main components, and adds pre-made masterbatch A, polymer adhesive modifier, chopped fibers, and other components. This significantly improves the heat resistance, steam molding bonding strength, and cell structure uniformity of the foamed material while maintaining good foaming processability, effectively solving the problem of balancing high heat resistance and easy adhesion in existing foamed materials. Specifically: First, this application introduces a small amount of homopolymer polypropylene, which has higher crystallinity, rigidity, and heat resistance than random copolymer PP. This significantly improves the heat distortion temperature of the foamed material, expanding its application range in areas such as automotive hood components and high-temperature packaging. Secondly, by pre-preparing masterbatch A through melt blending of random copolymer PP and polymer micropowder, the high-melting-point polymer micropowder is stretched and sheared during the twin-screw extrusion process of masterbatch A, forming a microfiber structure. These microfibers can be uniformly dispersed in the PP matrix, acting like a "skeleton" to significantly enhance melt strength and cell wall toughness. This effectively inhibits cell collapse and coalescence during foaming, resulting in foamed beads with uniform cell size and high closed-cell ratio. Furthermore, the addition of the chopped fibers further improves the material's heat resistance and flexural strength, while the introduction of a compatibilizer ensures good interfacial bonding between the fibers and polymer microfibers in the PP matrix, avoiding performance degradation caused by phase separation. Furthermore, the polymeric adhesive modifier has a melting point much lower than that of the PP matrix. It can selectively melt during the steam molding stage, wetting and promoting the diffusion and entanglement of molecular chains between the foamed bead interfaces. This allows high-heat-resistant PP foamed beads to be firmly bonded together using conventional steam molding processes without sacrificing overall heat resistance, achieving excellent mechanical strength. This effectively avoids the previous problems of high-heat-resistant foamed particles failing to form or producing loose products due to surface non-melting. In summary, this application, through the synergistic effect between its components, enables the final foamed material to simultaneously achieve high heat resistance, high melt strength, excellent steam adhesion, and a uniform and fine cell structure. Its comprehensive performance is significantly superior to existing technologies, demonstrating significant industrial application value.
[0008] In some embodiments, the weight ratio of the random copolymer polypropylene to the polymer powder can be (3-4):1 or (4-5):1.
[0009] In one specific implementation, the weight ratio of the random copolymer polypropylene to the polymer micropowder can be 3:1, 4:1, or 5:1.
[0010] Optionally, during the preparation of masterbatch A, the melting temperature is 180-240℃, the extrusion length-to-diameter ratio is (20-60):1, and the rotation speed of the extrusion equipment is 300-600 rpm.
[0011] Optionally, the melt index of the random copolymer polypropylene is 1-60 g / 10 min at 230℃ / 2.16 kg; and the melt index of the homopolymer polypropylene is 1-30 g / 10 min at 230℃ / 2.16 kg.
[0012] Optionally, the compatibilizer is maleic anhydride-grafted polyolefin, selected from one or more of maleic anhydride-grafted PP, maleic anhydride-grafted PE, maleic anhydride-grafted SEBS, and maleic anhydride-grafted POE.
[0013] Optionally, the polymeric adhesive modifier is selected from one or more of polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, and thermoplastic polyolefin elastomer.
[0014] Optionally, the nucleating agent is selected from one or more of silica, montmorillonite, talc, mica, sodium benzoate, sodium p-tert-butylbenzoate, and metal salt ion polymers.
[0015] Optionally, the chopped fiber is one or more of the following: surface-treated carbon fiber, glass fiber, polyester fiber, and aramid fiber, and the length of the chopped fiber is 2-6 mm.
[0016] Secondly, this application provides a method for preparing a high heat-resistant PP bead foam material, using a two-stage screw extruder, wherein the upper stage screw is a twin-screw extruder and the lower stage screw is a single-screw extruder; the preparation method specifically includes the following steps: Polypropylene, compatibilizer, polymer binder modifier and masterbatch A are mixed evenly and dried; then nucleating agent is added and mixed evenly to obtain premix; The premixed material is placed in the main feed hopper of the twin-screw extruder; the chopped fibers are placed in the side feed hopper of the twin-screw extruder; after melt blending in the upper stage twin-screw and steady-flow extrusion in the lower stage, the material is granulated and dried to obtain polypropylene raw material; Water is added to polypropylene raw materials, the temperature is raised to 130-170℃, and then a supercritical gas foaming agent is injected to a pressure of 2-10MPa. After rapid depressurization and foaming in 0.5-5s, high heat-resistant PP bead foam material is obtained.
[0017] This application effectively ensures the dispersion and integrity of fibers by adding short-cut fibers in the twin-screw conveying zone, and the orientation of fiber distribution is effectively ensured by the flow stabilization of the lower-stage single screw, further ensuring the uniformity of foam cells after foaming. If fibers are added at the front end of the twin screw, the strong shear of the twin screw meshing section will cut the fibers into pieces, resulting in uneven fiber length and disordered orientation, which in turn forms perforations and leads to uneven foam cell size after foaming.
[0018] Optionally, the supercritical gas blowing agent is selected from one or more of supercritical CO2, nitrogen, and argon.
[0019] Optionally, the length-to-diameter ratio of the upper-stage twin-screw extrusion is (20-60):1, the heating temperature is 180-230℃, and the extrusion equipment speed is 200-400rpm; The length-to-diameter ratio of the lower-stage single-screw extrusion is (10-30):1, the heating temperature is 180-240℃, and the extrusion equipment speed is 80-150rpm.
[0020] In summary, this application has the following beneficial effects: 1. In this application, a masterbatch A is prepared by first using random copolymer polypropylene and polymer micro powder in a weight ratio of (3-5):1. The masterbatch A is then melt-blended with random copolymer polypropylene and homopolymer polypropylene, polymer binder modifier, chopped fiber and other components in a specific weight ratio, and extruded and granulated to obtain a high heat-resistant PP bead foam material with excellent comprehensive properties. It has the advantages of high heat resistance, high melt strength, excellent vapor adhesion and uniform and fine cell structure, and has broad application prospects.
[0021] 2. The high heat-resistant PP bead foam material obtained in this application has a tensile strength of 2003-2256 kPa (≥2000 kPa) and a flexural strength of 3101-4017 kPa (≥3100 kPa) after steam molding, and a heat distortion temperature (HDT) of 113-131℃ (≥110℃). Attached Figure Description
[0022] Figure 1 This is a product image of the high heat-resistant PP bead foam material obtained in Example 2 of this application; Figure 2 This is a product image of the high heat-resistant PP bead foam material obtained in Comparative Example 13 of this application; Figure 3 This is a product image of the high heat-resistant PP bead foam material obtained in Comparative Example 4 of this application; Figure 4 This is a cell diagram of the high heat-resistant PP bead foam material obtained in Example 2 of this application; Figure 5 This is a cell diagram of the high heat-resistant PP bead foam material obtained in Comparative Example 13 of this application; Figure 6 This is a cell diagram of the high heat-resistant PP bead foam material obtained in Comparative Example 4 of this application. Detailed Implementation
[0023] This application provides a high heat-resistant PP bead foam material, comprising the following components in parts by weight: 100 parts polypropylene, 1-10 parts compatibilizer, 0.5-10 parts polymer binder modifier, 0.2-2 parts nucleating agent, 2-15 parts chopped fibers, and 5-20 parts masterbatch A; wherein the polypropylene comprises random copolymer polypropylene and homopolymer polypropylene in a weight ratio of (80-95):(5-20); This application also provides a method for preparing the above-mentioned high heat-resistant PP bead foam material, including the following steps: (1) Mix polypropylene, compatibilizer, polymer binder modifier and masterbatch A evenly and dry; then add nucleating agent and mix evenly to obtain premix; (2) Place the premixed material in the main feed hopper of the twin-screw extruder; place the chopped fiber in the side feed hopper of the twin-screw extruder; melt and mix through the upper twin-screw extruder, and then extrude it through the lower single screw extruder. After extrusion, granulation, and drying, polypropylene raw material is obtained. Among them, the length-to-diameter ratio of the upper-stage twin-screw extrusion is (20-60):1, the heating temperature is 180-230℃, and the extrusion equipment speed is 200-400rpm; The length-to-diameter ratio of the lower-stage single-screw extrusion is (10-30):1, the heating temperature is 180-240℃, and the extrusion equipment speed is 80-150rpm;
[0024] (3) Place the polypropylene raw material in a high-pressure foaming kettle, add water, and heat it to 130-170℃; then inject supercritical gas foaming agent to a pressure of 2-10MPa, and foam after rapid depressurization for 0.5-5s to obtain foamed particles. After dehydration by a dehydrator, obtain high heat-resistant PP bead foamed material.
[0025] In the embodiments of this application, the random copolymer polypropylene is Borealis RG468M0, with a melt index of 30g / 10min at 230℃ / 2.16kg; the homopolymer PP is Borealis WE100HMS, with a melt index of 10g / 10min at 230℃ / 2.16kg; the polyethylene is low-density linear polyethylene, brand name Sinopec DFDA-7042, and the ethylene-acrylic acid copolymer is Dow 5980I; the compatibilizer is maleic anhydride-grafted PP, brand name Mitsui ADMER F601; the polytetrafluoroethylene micro powder is brand name Daikin M112, and the polyethylene terephthalate is brand name China Resources bottle grade PET CR-8839; the chopped fiber is Changhai glass fiber PP-108, with a length of 4.5mm; the raw materials, reagents, solvents, etc. used in this application are all commercially available.
[0026] The present application will be further described in detail below with reference to preparation examples, embodiments, performance testing tests and accompanying drawings. Preparation Example 1
[0027] Preparation Example 1 provides a masterbatch A.
[0028] The preparation method of the above masterbatch A is as follows: 600g of random copolymer PP and 200g of polytetrafluoroethylene micro powder (particle size of 20-40μm) are mixed evenly and then placed in the feed hopper of a twin-screw extruder. The mixture is melt-mixed and extruded through the twin-screw extruder. The temperature zones of the twin-screw extruder are 220℃, the speed is 500r / min, and the length-to-diameter ratio is 45:1. After stretching, pelletizing, and drying, masterbatch A is obtained. Preparation Example 2
[0029] Preparation Example 2 provides a masterbatch A.
[0030] The preparation method of the above masterbatch A is as follows: 800g of random copolymer PP and 200g of polytetrafluoroethylene micro powder are mixed evenly, and then placed in the feed hopper of a twin-screw extruder. The mixture is melt-mixed and extruded through the twin-screw extruder, and then stretched, pelletized, and dried to obtain masterbatch A. Preparation Example 3
[0031] Preparation Example 3 provides a masterbatch A.
[0032] The preparation method of the above masterbatch A is as follows: 1000g of random copolymer PP and 200g of polytetrafluoroethylene micro powder are mixed evenly, and then placed in the feed hopper of a twin-screw extruder. The mixture is melt-mixed and extruded through the twin-screw extruder, and then stretched, pelletized, and dried to obtain masterbatch A. Preparation Example 4
[0033] Preparation Example 4 provides a masterbatch A.
[0034] The difference between the above preparation example and preparation example 2 is that the polytetrafluoroethylene micro powder is replaced with polyethylene terephthalate micro powder (particle size of 40-70 μm). Comparative Preparation Example 1
[0035] Comparative preparation example 1 provides a masterbatch A.
[0036] The preparation method of the above masterbatch A is as follows: 500g of random copolymer PP and 500g of polytetrafluoroethylene micro powder are mixed evenly, and then placed in the feed hopper of a twin-screw extruder. The mixture is melt-mixed and extruded through the twin-screw extruder, and then stretched, pelletized, and dried to obtain masterbatch A. Comparative Preparation Example 2
[0037] Comparative preparation example 2 provides a masterbatch A.
[0038] The preparation method of the above masterbatch A is as follows: 700g of random copolymer PP and 100g of polytetrafluoroethylene micro powder are mixed evenly, and then placed in the feed hopper of a twin-screw extruder. The mixture is melt-mixed and extruded through the twin-screw extruder, and then stretched, pelletized, and dried to obtain masterbatch A. Comparative preparation example 3
[0039] Comparative preparation example 3 provides a masterbatch A.
[0040] The difference between the above comparative preparation example and preparation example 2 is that the polytetrafluoroethylene micro powder was replaced with polyethylene terephthalate micro powder (particle size of 500-1000 μm). Examples 1-4
[0041] Examples 1-4 provide a high heat-resistant PP bead foam material.
[0042] The difference between the above embodiments is that the masterbatch A used in Examples 1-4 was derived from Preparation Examples 1-4.
[0043] The preparation method of the high heat-resistant PP bead foam material provided in Examples 1-4 includes the following steps: (1) Mix 900g random copolymer polypropylene, 100g homopolymer polypropylene, 30g maleic anhydride grafted PP, 40g low-density linear polyethylene and 100g masterbatch A evenly and dry; then add 10g talc powder and mix evenly to obtain a premix. (2) Place the above premixed material in the main feed hopper of a twin-screw extruder; place 80g of glass fiber in the side feed hopper of a twin-screw extruder; melt and mix through the upper twin-screw extruder, and then extrude through the lower single screw extruder. After extrusion, pelletizing, and drying, polypropylene raw material is obtained. The upper-stage twin-screw extruder has a length-to-diameter ratio of 45:1 and 13 heating zones. The temperatures of each zone from the feed port to the die head are as follows: Zone 1: 200℃, Zone 2: 220℃, Zone 3: 220℃, Zone 4: 220℃, Zone 5: 230℃, Zone 6: 230℃, Zone 7: 210℃, Zone 8: 210℃, Zone 9: 210℃, Zone 10: 190℃, Zone 11: 190℃, Zone 12: 190℃, and Zone 13: 190℃. The screw speed of the twin-screw extruder is 250 rpm. The side feeding position is in Zone 10, and there is no meshing section between the side feeding zone and the discharge port; this section is the conveying zone. The lower-stage single-screw extruder has a length-to-diameter ratio of 25:1 and eight heating zones. The temperatures of each zone from the feed port to the die head are as follows: Zone 1: 210℃, Zone 2: 210℃, Zone 3: 200℃, Zone 4: 200℃, Zone 5: 190℃, Zone 6: 190℃, Zone 7: 190℃, and Zone 8: 200℃. The single-screw extruder rotates at 120 rpm. (3) Place 200g of polypropylene raw material in a 29L high-pressure foaming kettle, add 20L of water, and heat to 158℃; then inject supercritical gas foaming agent CO2 to a pressure of 4.5MPa, and foam after 2s of rapid depressurization to obtain foamed particles. After dehydration by a dehydrator, obtain high heat-resistant PP bead foamed material. Example 5
[0044] Example 5 provides a high heat-resistant PP bead foam material.
[0045] The difference between this embodiment and Embodiment 2 is that the amount of random copolymer polypropylene added is 800g and the amount of homopolymer polypropylene added is 200g. Example 6
[0046] Example 6 provides a high heat-resistant PP bead foam material.
[0047] The difference between this embodiment and Embodiment 2 is that the amount of random copolymer polypropylene added is 850g and the amount of homopolymer polypropylene added is 150g. Example 7
[0048] Example 7 provides a high heat-resistant PP bead foam material.
[0049] The difference between this embodiment and Embodiment 2 is that the amount of random copolymer polypropylene added is 950g and the amount of homopolymer polypropylene added is 50g. Example 8
[0050] Example 8 provides a high heat-resistant PP bead foam material.
[0051] The difference between this embodiment and Embodiment 2 is that the amount of masterbatch A added is 50g. Example 9
[0052] Example 9 provides a high heat-resistant PP bead foam material.
[0053] The difference between this embodiment and Embodiment 2 is that the amount of masterbatch A added is 200g. Example 10
[0054] Example 10 provides a high heat-resistant PP bead foam material.
[0055] The difference between the above embodiment and Embodiment 2 is that the amount of low-density linear polyethylene added is 80g. Example 11
[0056] Example 11 provides a high heat-resistant PP bead foam material.
[0057] The difference between this embodiment and Embodiment 2 is that the low-density linear polyethylene is replaced with ethylene-acrylic acid copolymer. Example 12
[0058] Example 12 provides a high heat-resistant PP bead foam material.
[0059] The difference between this embodiment and Embodiment 2 is that the amount of chopped fiber added is 150g. Comparative Examples 1-3
[0060] Comparative Examples 1-3 each provide a high heat-resistant PP bead foam material.
[0061] The difference between the above comparative examples and Example 2 is that the masterbatch A used in comparative examples 1-3 was derived from comparative preparation examples 1-3. Comparative Example 4
[0062] Comparative Example 4 provides a high heat-resistant PP bead foam material.
[0063] The difference between this comparative example and Example 2 is that the amount of masterbatch A added is 0. Comparative Example 5
[0064] Comparative Example 5 provides a high heat-resistant PP bead foam material.
[0065] The difference between this comparative example and Example 2 is that the amount of masterbatch A added is 300g. Comparative Example 6
[0066] Comparative Example 6 provides a high heat-resistant PP bead foam material.
[0067] The difference between this comparative example and Example 2 is that the homopolymer polypropylene is replaced with an equal amount of random copolymer polypropylene. Comparative Example 7
[0068] Comparative Example 7 provides a high heat-resistant PP bead foam material.
[0069] The difference between this comparative example and Example 2 is that the amount of random copolymer polypropylene added is 750g and the amount of homopolymer polypropylene added is 250g. Comparative Example 8
[0070] Comparative Example 8 provides a high heat-resistant PP bead foam material.
[0071] The difference between this comparative example and Example 2 is that the amount of polymeric adhesive modifier (low-density linear polyethylene) added is 0. Comparative Example 9
[0072] Comparative Example 9 provides a high heat-resistant PP bead foam material.
[0073] The difference between this comparative example and Example 2 is that the amount of polymeric adhesive modifier (low-density linear polyethylene) added is 150g. Comparative Example 10
[0074] Comparative Example 10 provides a high heat-resistant PP bead foam material.
[0075] The difference between this comparative example and Example 2 is that the amount of chopped fiber added is 0. Comparative Example 11
[0076] Comparative Example 11 provides a high heat-resistant PP bead foam material.
[0077] The difference between this comparative example and Example 2 is that the amount of chopped fiber added is 200g. Comparative Example 12
[0078] Comparative Example 12 provides a high heat-resistant PP bead foam material.
[0079] The difference between this comparative example and Example 2 is that the amount of compatibilizer (maleic anhydride-grafted PP) added is 0. Comparative Example 13
[0080] Comparative Example 13 provides a high heat-resistant PP bead foam material.
[0081] The difference between this comparative example and Example 2 is that the chopped fibers are mixed into the premix in step (1) and added to the main feed hopper of the two-stage screw extruder in step (2). Comparative Example 14
[0082] Comparative Example 14 provides a high heat-resistant PP bead foam material.
[0083] The difference between this comparative example and Example 2 is that 100g of masterbatch A was replaced with 20g of polytetrafluoroethylene micro powder. Comparative Example 15
[0084] Comparative Example 15 provides a high heat-resistant PP bead foam material.
[0085] The difference between this comparative example and Example 2 is that the screw speed of the twin-screw extruder is adjusted to 500 rpm.
[0086] Performance testing The high heat-resistant PP bead foam materials prepared in Examples 1-12 and Comparative Examples 1-15 were steam-formed using a steam forming machine (mold A or mold B) to obtain test specimen A or test specimen B. Various performance tests were performed on the test specimens, and the results are shown in Table 1-2 below.
[0087] Steam forming mold A adopts the tensile specimen size design in GB 9641-1988 "Test Method for Tensile Properties of Rigid Foamed Plastics" with a thickness of 10mm; mold B is a 400×400mm square mold with a thickness of 6mm.
[0088] The performance testing methods are as follows (all tests were conducted at 23±1℃ and 50±5%RH): (1) Foaming density: The foaming density of the foamed beads was determined according to GB / T 6343-2009 "Determination of apparent density of foamed plastics and rubber"; (2) Tensile strength: The tensile strength of test specimen A was determined according to GB 9641-1988 "Test Method for Tensile Properties of Rigid Foamed Plastics"; (3) Bending strength: The bending strength of sample B was tested according to GB / T 8812.2-2007 "Determination of bending properties of rigid foamed plastics"; (4) Heat resistance: The heat distortion temperature (HDT) of sample B was tested according to GB / T 1634.2 "Plastics: Determination of temperature of deformation under load - Part 2: Plastics, hard rubber and long fiber reinforced composites"; (5) Steam adhesion: Steam adhesion is evaluated by visual inspection and tensile strength; (6) Uniformity of bubbles: Visually observe whether the bubbles are fine, uniform in size, and without collapsed bubbles.
[0089] Table 1. Performance test results of the foamed materials in Examples 1-12 after molding.
[0090] Table 2. Performance test results of the foamed materials in Comparative Examples 1-15 after molding.
[0091] The results of Examples 1-3 and Comparative Examples 1-2 show that in Comparative Example 1, the weight ratio of random copolymer polypropylene to polymer micropowder was controlled at 1:1, and the resulting PP bead foam material could not be steam bonded and molded. In Comparative Example 2, the weight ratio of random copolymer polypropylene to polymer micropowder was controlled at 7:1, and the resulting PP bead foam material had poor bonding and molding, with local cracking. However, in Examples 1-3, the weight ratio of random copolymer polypropylene to polymer micropowder was controlled within the range of (3-5):1, which resulted in high heat-resistant PP bead foam material with good cell uniformity, heat resistance, and toughness.
[0092] The results of Examples 2, 4 and Comparative Example 3 show that the particle size of the micro powder affects the in-situ fiber formation effect. Excessively large particle size will make fiber formation difficult and thus affect the foaming performance of the material, resulting in uneven cell size and thus affecting the molding performance.
[0093] The test results of Examples 2, 5-7 and Comparative Examples 6-7 show that the introduction of homopolymer PP can significantly improve the heat resistance and rigidity of the material. However, with excessive addition, the material becomes too rigid and heat-resistant, resulting in poor vapor adhesion. Although the surface can be molded, the internal particle adhesion is poor, leading to a decrease in tensile strength after molding. The test results of Examples 2, 8-10 and Comparative Examples 4-5 show that introducing high melting point micro powder into pre-made masterbatch A can improve the foaming performance of the material, increase the uniformity of the cell structure, and improve the heat resistance of the material. However, excessive micro powder will lead to a decrease in the foaming and steam bonding performance of the material.
[0094] The test results of Examples 2, 11, and 9 show that the introduction of polymeric adhesive modifiers can improve the vapor adhesion of materials, but excessively high content will rapidly reduce the heat resistance of materials.
[0095] The test results of Examples 2, 12, and Comparative Examples 10-11 show that the introduction of glass fiber can improve the heat resistance and rigidity of the material, but excessive fiber content will make the material foaming and molding difficult.
[0096] The test results of Example 2 and Comparative Example 12 show that the use of compatibilizer can improve the compatibility between PP and each added phase, and improve the foaming performance of the material.
[0097] The test results of Example 2 and Comparative Example 13 show that adding glass fiber during the premixing stage will cause fiber breakage and disordered dispersion due to the high shear of the twin-screw extruder, which will affect the foaming performance and vapor adhesion of the material.
[0098] The test results of Examples 2 and Comparative Examples 14-15 show that adding polymer micropowder in the form of masterbatch can greatly improve the dispersibility of micropowder and the formation of microfibers. Direct mixing will lead to uneven dispersion of micropowder, which in turn will affect the foaming performance of the material.
[0099] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A high heat-resistant PP bead foam material, characterized in that, It includes the following components in parts by weight: 100 parts polypropylene, 1-10 parts compatibilizer, 0.5-10 parts polymer binder modifier, 0.2-2 parts nucleating agent, 2-15 parts chopped fibers, and 5-20 parts masterbatch A; The polypropylene includes random copolymer polypropylene and homopolymer polypropylene in a weight ratio of (80-95):(5-20); The masterbatch A is obtained by melt blending random copolymer polypropylene and polymer micro powder in a weight ratio of (3-5):1, extrusion granulation and drying. The polymer micro powder is selected from one or more of polytetrafluoroethylene micro powder, polyethylene terephthalate micro powder, polybutylene terephthalate micro powder, and polyamide micro powder; the particle size of the polymer micro powder is 10-100 μm.
2. The high heat-resistant PP bead foam material according to claim 1, characterized in that, During the preparation of masterbatch A, the melting temperature is 180-240℃, the extrusion length-to-diameter ratio is (20-60):1, and the rotation speed of the extrusion equipment is 300-600 rpm.
3. The high heat-resistant PP bead foam material according to claim 1, characterized in that, The compatibilizer is maleic anhydride-grafted polyolefin, selected from one or more of maleic anhydride-grafted PP, maleic anhydride-grafted PE, maleic anhydride-grafted SEBS, and maleic anhydride-grafted POE.
4. The high heat-resistant PP bead foam material according to claim 1, characterized in that, The polymeric adhesive modifier is selected from one or more of polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, and thermoplastic polyolefin elastomer.
5. The high heat-resistant PP bead foam material according to claim 1, characterized in that, The nucleating agent is selected from one or more of silica, montmorillonite, talc, mica, sodium benzoate, sodium p-tert-butylbenzoate, and metal salt ion polymers.
6. The high heat-resistant PP bead foam material according to claim 1, characterized in that, The chopped fibers are one or more of the following: surface-treated carbon fiber, glass fiber, polyester fiber, and aramid fiber, with a length of 2-6 mm.
7. The method for preparing the high heat-resistant PP bead foam material according to any one of claims 1-6, characterized in that, The preparation is carried out using a two-stage screw extrusion apparatus, wherein the upper stage screw is a twin-screw extruder and the lower stage screw is a single-screw extruder; the specific preparation method includes the following steps: Polypropylene, compatibilizer, polymer binder modifier and masterbatch A are mixed evenly and dried; then nucleating agent is added and mixed evenly to obtain premix; The premixed material is placed in the main feed hopper of the twin-screw extruder; the chopped fibers are placed in the side feed hopper of the twin-screw extruder; after melt blending in the upper stage twin-screw and steady-flow extrusion in the lower stage, the material is granulated and dried to obtain polypropylene raw material; Water is added to polypropylene raw materials, the temperature is raised to 130-170℃, and then a supercritical gas foaming agent is injected to a pressure of 2-10MPa. After rapid depressurization and foaming in 0.5-5s, high heat-resistant PP bead foam material is obtained.
8. The method for preparing high heat-resistant PP bead foam material according to claim 7, characterized in that, The supercritical gas foaming agent is selected from one or more of supercritical CO2, nitrogen, and argon.
9. The method for preparing high heat-resistant PP bead foam material according to claim 7, characterized in that, The length-to-diameter ratio of the upper-stage twin-screw extrusion is (20-60):1, the heating temperature is 180-230℃, and the extrusion equipment speed is 200-400rpm; The length-to-diameter ratio of the lower-stage single-screw extrusion is (10-30):1, the heating temperature is 180-240℃, and the extrusion equipment speed is 80-150rpm.